THE STYLE OF PARANA'S NEWSPAPERS: A SEMIOTIC APPROACH - Silva, Fernando Moreno da [UNESP]; Pinto, Samantha Isabela (Univ Estado Mato Grosso, 2016)
This article aims to analyze the style of printed journalism in the state of Parana. For this, as a criterion for the formation of the corpus, the choice focused on two printed newspaper of largest circulation in the state. Based on the statistics of circulation presented by the National Newspaper Association, the following newspapers were chosen: Folha de Londrina and Gazeta do Povo. As a theoretical support, it is used the French semiotics, focusing on the relationship between enunciator and enunciatee from enunciative studies. The analysis proved that these newspapers have different styles: from one side, Folha de Londrina is characterized for being a small-town newspaper with a popular, simple and cool reader; from the other, Gazeta do Povo, which is a refined newspaper read by a critic public.
Keywords: enunciation; style; Folha de Londrina; Gazeta do Povo